A Framework of Entrepreneurship Incubator for Indigenous Youth to Become Successful Entrepreneurs - Amiruddin, Mohd Hasril; Suib, Siti Normah; Sri Sumarwati; Razali, Nizamuddin; Hamzah, Usuloudin (Online Journal for TVET Practitioners, 2021)
Abstract The involvement of indigenous peoples in entrepreneurship through assistance and guidance to entrepreneurs with technical and vocational-based training seeks to help them deal with the issue of high levels of poverty, education issues, and mind change to continue to compete in this challenging globalization era. This study aims to identify the factors that motivate indigenous youths to engage in entrepreneurship including the internal and external aspects that are appropriate to produce business incubators framework for indigenous youths through technical and vocational training. This study is a qualitative study involving 10 experts, who have been selected using purposive sampling. Data were obtained based on semi-structured interviews, which were further analyzed using thematic analysis to identify emerging themes. Finding found that the eight success factors were external support factors include financial, mentoring and business advice, networking, government policies, and stakeholder objectives, research – university, entrepreneurial education and entrepreneurial skill, physical and logistical infrastructure, and technology support. Internal support factors include the demographic, field of entrepreneurship, and characteristics of entrepreneurs. In the future, the researchers will continue to perform a pilot test and an actual study and then analyze the result of the research hypotheses.